The Newer Greek Text of the New Testament (NA28 and UBS5) and Its Implications for Translation - Scholz, Vilson (The Bible translator, 2021)
Compared to the previous editions of the Greek New Testament, Nestle–Aland27 and UBS4, the newer editions (NA28 and UBS5) present some thirty-four changes, specifically in the Catholic Epistles. To what extent will this impact the translation of the New Testament? This paper will show that in half of those instances there will be some implication for translators and revisers of the New Testament.